USE OF MACROMEDIA FLASH 8 LEARNING MEDIA TO INCREASE STUDENTS' INTEREST IN LEARNING IN INFORMATICS SUBJECT CLASS X SMAN 5 SERANG CITY - Ardana, Atikoh; Junedi, Beni; Ficticarani, Ade (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The aim of this study is to find out the significant differences in the use of Macromedia Flash 8-based learning media in Informatics subjects on the learning interest of class X SMAN 5 Serang City students compared to conventional learning methods. The method used is a quantitative experiment. Observations show that the majority of students have low interest in learning, which has an impact on their learning outcomes. The research results show that the R Square value is 97.8%, indicating that the learning media variable influences interest in learning (Y), namely 97.8%. The average score of the control class was 90.52, then the experimental class reached 137.82, showing higher interest in learning in the experimental class. The independent sample test shows a significance value of 0.008 < 0.05, so Ha is accepted, indicating that there is a significant difference between the control and experimental classes. This study proves that the use of Macromedia Flash 8 increases students' interest in learning in Informatics lessons.